On bubble rise dynamics in a continuum and pairwise interaction: an experimental and numerical study - Al-Behadili, Mustapha Abbas Ethaib (2017)
The wide range of applications of bubbly flows in the industry makes its accurate modelling strongly demanded. The modelling of bubbly flow, however, is not straightforward because it consists of multi-scale structures in both time and space. Furthermore, the experimental verifications of the theoretical and the Direct Numerical Simulations, DNS, available are noticeably scarce especially for bubbles at high Reynolds numbers. Hence, this research aims to make its contribution to addressing the basic roots that make the modelling process difficult. These roots are represented, but not limited, by the bubble dynamics and bubble-bubble interaction. Tracking of single and dual air bubbles in quiescent water is experimentally carried out using a high-speed camera. For the numerical simulations, using ANSYS-FLUENT software with the VOF model, a structured adaptive mesh technique was developed here that is used to achieve a desirable level of refinement of the mesh around the rising bubbles. It has been found that there is a relationship between the lateral migration of an ellipsoidal bubble and the shape oscillation. This relationship, however, has not been observed for the numerical approach. It also overestimated the experimental findings of bubble kinetics and shape oscillation by 30%. Interestingly, this research contributes to awakening the small details in the underlying physics of the interaction between a pair of rising bubbles. It has been found that a slight deviation in the size of a trailing bubble plays an important role in the state of the trailing bubble whether it approaches the leading bubble or separates from at large separation distances. This is considered due to the greater rise velocity that a smaller bubble has in the ellipsoidal regime compared to the larger bubble. Furthermore, when the separation distance between the rising bubbles is decreased, the appreciable acceleration that the trailing bubble owns has led it to approach the leading bubble and coalesce with it. This behaviour is supported by experiments and by the good agreement that the numerical approach showed. An empirical model that predicts the coalescence rate based on the deviation in the size ratio is presented. Finally, the spatial boundaries over which the coalescence of bubble pairs might occur has been numerically and experimentally presented.